A comparative study of various ETL process and their testing techniques in data warehouse. Issue 4 (4th July 2017) - Vyas, Sonali; Vaishnav, Pragya
Abstract: Extraction–transformation–loading (ETL) tools are fraction of software which extract the data from various sources, and then it clean, customize, reformat, and integrate the data and insert into a data warehouse. ETL process in data warehousing responsible for pick data out from the operational systems and fixed it into the data warehouse. Construct the ETL process is one of the bulky tasks of construct a warehouse. In this paper we will try to explain the ETL process, ETL testing challenges and ETL testing techniques.